The role of intra- and inter-site exchange correlations in the extended Falicov–Kimball model on a triangular lattice. (February 2016) - Kumar, Sant; Yadav, Umesh K.; Maitra, T.; Singh, Ishwar
Abstract: Ground state magnetic properties of the spin-dependent Falicov–Kimball model (FKM) are studied by incorporating the intrasite exchange correlation J (between itinerant d - and localized f -electrons) and intersite (superexchange) correlation J se (between localized f -electrons) on a triangular lattice for two different fillings. Numerical diagonalization and Monte-Carlo techniques are used to determine the ground state magnetic properties. Transitions from antiferromagnetic to ferromagnetic and again to re-entrant antiferromagnetic phase is observed in a wide range of parameter space. The magnetic moments of d - and f -electrons are observed to depend strongly on the value of J, J se and also on the total number of d -electrons ( N d ). Abstract : Highlights: Ground state magnetic properties for Spin-1/2 FKM on a triangular lattice are studied. Numerical diagonalization with classical Monte-Carlo simulation algorithm is used. Inclusion of super-exchange interaction J se gives rise to many interesting phases. Numerical results are relevant for the systems like GdI2, NaTiO2 and NaVO2, etc.